Antioxidant Sol-Gel Improves Cutaneous Wound Healing in Streptozotocin-Induced Diabetic Rats. (7th August 2012) - Lee, Yen-Hsien; Chang, Jung-Jhih; Chien, Chiang-Ting; Yang, Ming-Chien; Chien, Hsiung-Fei
Abstract : We examined the effects of vitamin C in Pluronic F127 on diabetic wound healing. Full-thickness excision skin wounds were made in normal and diabetic Wistar rats to evaluate the effect of saline, saline plus vitamin C (antioxidant sol), Pluronic F127, or Pluronic F127 plus vitamin C (antioxidant sol-gel). The rate of wound contraction, the levels of epidermal and dermal maturation, collagen synthesis, and apoptosis production in the wound tissue were determined. In vitro data showed that after 6 hours of air exposure, the order of the scavenging abilities for HOCl, H 2 O 2, and O 2 - was antioxidant sol-gel > antioxidant saline > Pluronic F127 = saline. After 7 and 14 days of wound injury, the antioxidant sol-gel improved wound healing significantly by accelerated epidermal and dermal maturation, an increase in collagen content, and a decrease in apoptosis formation. However, the wounds of all treatments healed mostly at 3 weeks. Vitamin C in Pluronic F127 hastened cutaneous wound healing by its antioxidant and antiapoptotic mechanisms through a good drug delivery system. This study showed that Pluronic F127 plus vitamin C could potentially be employed as a novel wound-healing enhancer.